Effects of two different volume-equated weekly distributed short-term plyometric training programs on futsal players' physical performance - Yanci, J.; Castillo, D.; Iturricastillo, A.; Ayarra, R.; Nakamura, F. Y. (The Journal of Strength and Conditioning Research, 2017)
The aim was to analyze the effect of 2 different plyometric training programs (i.e., 1 vs. 2 sessions per week, same total weekly volume) on physical performance in futsal players. Forty-four futsal players were divided into 3 training groups differing in weekly plyometric training load: the 2 days per week plyometric training group (PT2D, n = 15), the 1 day per week plyometric training group (PT1D, n = 12), and the control group (CG, n = 12) which did not perform plyometric training. The results of this study showed that in-season futsal training per se was capable of improving repeat sprint ability (RSA) (effect size [ES] = -0.59 to -1.53). However, while change of direction ability (CODA) was maintained during the training period (ES = 0.00), 15-m sprint (ES = 0.73), and vertical jump (VJ) performance (ES = -0.30 to -1.37) were significantly impaired. By contrast, PT2D and PT1D plyometric training were effective in improving futsal players' 15-m sprint (ES = -0.64 to -1.00), CODA (ES = -1.83 to -5.50), and horizontal jump (ES = 0.33-0.64) performance. Nonetheless, all groups (i.e., PT2D, PT1D, and CG) presented a reduction in VJ performance (ES = -0.04 to -1.37). Regarding RSA performance, PT1D showed a similar improvement compared with CG (ES = -0.65 to -1.53) after the training intervention, whereas PT2D did not show significant change (ES = -0.04 to -0.38). These results may have considerable practical relevance for the optimal design of plyometric training programs for futsal players, given that a 1-day-per-week plyometric training program is more efficient than a 2-day-per-week plyometric training program to improve the futsal players' physical performance.